Ground-State Structures of Hydrated Calcium Ion Clusters From Comprehensive Genetic Algorithm Search - Shi, Ruili; Zhao, Zhi; Huang, Xiaoming; Wang, Pengju; Su, Yan; Sai, Linwei; Liang, Xiaoqing; Han, Haiyan; Zhao, Jijun (Frontiers in Chemistry, 2021)
We search the lowest-energy structures of hydrated calcium ion clusters Ca2+(H2O)n (n = 10-18) in the whole potential energy surface by comprehensive genetic algorithm (CGA) combined with DMol3 package. The lowest-energy structures of Ca2+(H2O)10-12 clusters show that the Ca2+ is always surrounded by six H2O molecular in the first shell. The number of the first-shell water molecules changes from 6 to 8 at n = 12. In the range of n = 12-18, the number of the first-shell water molecules fluctuates between 7 and 8, meaning that the cluster could pack the water molecules in outer shell even though the inner shell is not full. Meanwhile, the number of the water molecules in the second shell and the total hydrogen bonds increases with the increase of cluster size. The distance between the Ca2+ and the adjacent water molecules increases while the average adjacent O-O distance decreases as the cluster size increasing, indicating that the interaction between the Ca2+ and the adjacent water molecules becomes weaker and the interaction between water molecules becomes stronger. The interaction energy and natural bond orbital (NBO) results show that the interaction between the Ca2+ and the water molecules mainly derive from the interaction between the Ca2+ and the adjacent water molecules. The charge transfer from the lone pair electron orbital of adjacent oxygen atoms to the lone pair empty electron orbital of the Ca2+ plays a leading role of the interaction between the Ca2+ and water molecules.